What does resilience sound like? Coral reef and dry forest acoustic communities respond differently to Hurricane Maria. (July 2021) - Gottesman, Benjamin L.; Olson, Jack C.; Yang, Soohyun; Acevedo-Charry, Orlando; Francomano, Dante; Martinez, Felix A.; Appeldoorn, Richard S.; Mason, Doran M.; Weil, Ernesto; Pijanowski, Bryan C.
Highlights: Soundscapes can help to measure dimensions of ecological resilience. Degree of soundscape alteration correlated with disturbance magnitude. Degree of soundscape alteration corresponded with distance to shoreline. Soundscapes became more variable after Hurricane Maria. Maria impacted animal communities at dry forest sites more than at coral reefs sites. Abstract: Disturbance regimes and biodiversity—two factors that govern the stability of ecosystems—are changing rapidly due to anthropogenic forces including climate change. Determining whether ecosystems retain their structure and function through intensifying disturbance regimes is an urgent task. However, quantitatively assessing the resilience of natural systems is a complex and challenging endeavor, especially for animal communities, for which datasets around disturbance events are scarce. Here, we apply an emerging remote sensing technology—the recording and analysis of soundscapes—to quantify the resilience of Puerto Rican coral reef and dry forest animal communities in relation to Hurricane Maria, which struck the island in September 2017. Using recordings collected between March 2017 and January 2018 at three terrestrial and three marine sites, we measured three dimensions of resilience—the magnitude of the impacts (resistance), the spatial pattern of the impacts (heterogeneity), and the diversity and timeline of functional responses (recovery)—across eight sound types representing different broad taxonomic groups. While the coral reef communities exhibited high resistance to the storm, all sound types within the dry forest were significantly impacted, with two of the three insect choruses and bird vocalizations at dawn declining approximately 50% in the weeks following Hurricane Maria. The mid-frequency insect sound type returned to pre-storm levels after 56 days, while bird vocalizations returned after 67 days, though seasonal and lunar patterns underscored the importance of long-term data for accurately measuring trajectories of recovery. This study demonstrates that soundscape methodologies can help to quantify elusive dimensions of animal community resilience in order to better understand how biodiversity and ecosystem functioning will change under novel disturbance regimes.